2020
DOI: 10.1093/brain/awaa263
|View full text |Cite|
|
Sign up to set email alerts
|

A novel RFC1 repeat motif (ACAGG) in two Asia-Pacific CANVAS families

Abstract: Cerebellar ataxia, neuropathy and vestibular areflexia syndrome (CANVAS) is a progressive late-onset, neurological disease. Recently, a pentanucleotide expansion in intron 2 of RFC1 was identified as the genetic cause of CANVAS. We screened an Asian-Pacific cohort for CANVAS and identified a novel RFC1 repeat expansion motif, (ACAGG)exp, in three affected individuals. This motif was associated with additional clinical features including fasciculations and elevated serum creatine kinase. These features have not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 22 publications
5
72
1
Order By: Relevance
“…The mechanism of disease caused by these interruptions is difficult to discern; further genotyping of these regions is first required. This complex motif structure is commonly seen in several newly discovered pentanucleotide repeat expansions such as RFC1 or SAMD12 , which show that pathogenic sequences are often extremely dynamic in nature [ 3 , 107 , 138 ].…”
Section: General Characteristics Of Repeat Expansion Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of disease caused by these interruptions is difficult to discern; further genotyping of these regions is first required. This complex motif structure is commonly seen in several newly discovered pentanucleotide repeat expansions such as RFC1 or SAMD12 , which show that pathogenic sequences are often extremely dynamic in nature [ 3 , 107 , 138 ].…”
Section: General Characteristics Of Repeat Expansion Disordersmentioning
confidence: 99%
“…Recently, more novel pathogenic RFC1 conformations have been implicated with CANVAS. ‘ACAGG’ was found to have expanded in two Asia–Pacific families [ 138 ] who demonstrated additional clinical features, namely fasciculations and elevated serum kinase. Another study showed a ‘(AAAGG) 10–25 (AAGGG) exp ’ allele was the predominant pathogenic allele found in Māori populations, with no apparent phenotypic differences when compared to the European populations [ 11 ].…”
Section: Recent Discoveries For Neurological Repeat Expansion Disordersmentioning
confidence: 99%
“…The size of the repeat is much larger in (AAGGG) exp alleles, which can reach more than 1,000 units than in (AAAGG) n alleles in the expansion range, that are below 1,000 repeats; most of the (AAAAG) n large alleles have less than 200 units [ 32 ]. Three additional repeat structures, AGAGG, AAGAG, and ACAGG have been observed in adult-onset ataxia cases [ 129 , 130 ], as well as a new allele with an (AAAGG) 10-25 tract preceding the (AAGGG) n [ 131 ] further showing the unstable nature of this repeat, being advisable to give careful attention to its sequence and size before releasing a molecular diagnosis.…”
Section: Biallelic Rfc1 Aaggg Expansions In Canvasmentioning
confidence: 99%
“…More recently, novel pathogenic (AAAGG)10-25(AAGGG)exp(AAAGG)4-6 and (ACAGG)exp configurations were identified individual from Oceania and East Asia (15)(16)(17).…”
Section: Identification Rfc1 Expansion Causing Canvas Late-onset Ataxia and Sensory Neuro(no)pathymentioning
confidence: 99%